Evaluación de formaciones para un descubrimiento de gas seco en el Caribe Colombiano, incorporando soluciones inversas, a partir de respuestas a modelos numéricos y analíticos (2017)
Currently, dry gas deposits have become very important in the oil industry, due to the increase in gas consumption in Colombia in the last 10 years. The demand for natural gas responds to factors such as population and industrial growth and the replacement of liquid fuel for transportation of vehicles or their use as alternative fuel in power generation plants. As a consequence of this, companies in the industry have focused on targeting their prospective portfolio in the Colombian Caribbean offshore in order to meet these needs in the future. Within Ecopetrol SA exploration projects, there is an accumulation of hydrocarbon (dry gas) in the Guajira Offshore Basin, which was found through the drilling of the CDG-1 Exploration Well (an alternative name is used to the Well in this grade project to reserve technical information about the Company and well´s location). From this well is information of well logging, samples of fluids and coring.